Efektivitas Penerapan Inquiry Teaching Model Terhadap Penilaian Tengah Semester Dalam Pembelajaran Pjok di SMP 4 Sejahtera Dramaga - Gumilang, Ryan Chandra; Ramadhan, Fajar; Dermawan, Dikdik Fauzi (Peneliti.net, 2024)
The Inquiry Teaching Model paradigm uses pre-experimental methods and techniques for learning. The heuristic strategy approach is a learning method that emphasizes student participation to encourage the development of critical thinking skills. Another description of the heuristic learning approach is that it is a series of activities designed to help students develop the habit of using analytical and critical thinking to solve problems. One approach to learning that uses issues as a means of